Characteristics of Speech Delay in Children Aged 2-5 Years for the Period January-December 2022 at RSUP Dr. Wahidin Sudirohusodo - Habsad, Dina Izaida; Maharani, Ratih Natasha; Darma, Sidrah; Darussalam, Andi Husni Esa; Jafar, Muh. Alfian (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The most common developmental disorder found in children is speech delay. The prevalence of symptoms of speech delay in children is 5-10% in Indonesia. This study aims to determine the characteristics of Speech Delay in children aged 2-5 years for the period January-December 2022 at RSUP Dr. Wahidin Sudirohusodo. Descriptive observational research method taken from secondary data (medical records). Results of research on children with Speech Delay aged 2-5 years for the period January-December 2022 at RSUP Dr. Wahidin Sudirohusodo is dominated by 2 and 3 year olds (36.9%), male (72.3%), father with higher education (98.5%), mother with higher education (95.4%), working father (100%), mothers do not work (50.8%), children ranked first (58.5%), with the most comorbidities Mixed Developmental Delay (24.6%). In conclusion, the majority of children aged 2 and 3 years, are male, have high parental education, the father's job is working and the mother's job is not working, the order of the first child and is dominated by the comorbidity Mix Developmental Delay.